Color Stability of Different Denture Teeth Following Immersion in Staining Solutions - Marzieh Ehsani; Leyla Sadighpour; Farideh Geramipanah; Azita Ehsani; Sima Shahabi (Tehran University of Medical Sciences, 2022)
Objectives: This study aimed to assess the color change (∆E00) of 7 brands of denture teeth (conventional acrylic and composite teeth) following immersion in staining solutions. Materials and Methods: Maxillary central incisor denture teeth made of 4 conventional acrylic resins (Vitapan, SR Vivodent PE, Beta Star and Crystal) and 3 composite resins (Finex, Emeral and Phonares II) were randomly divided into four groups (n=5). Denture teeth of different brands were immersed in tea, coffee, cola, and turmeric solutions. The solutions were incubated at 37°C. The baseline color of the teeth was measured using an intraoral spectrophotometer. The color of the teeth was measured after 24 h (∆E12), 1 week (∆E13), 2 weeks (∆E14), and 1 month (∆E15). ∆E00 was calculated and analyzed using one-way ANOVA. Pairwise comparisons were performed by the Tukey's post-hoc test (P<0.05). Results: The color stability of all teeth was significantly affected by the solutions (P<0.001). The type of tooth and coloring solution had significant interactions at all times (P<0.05). Turmeric caused the maximum color change in all teeth after 1 month. Repeated measures ANOVA showed that ∆E00 of all teeth was significantly affected by the duration of immersion in the solutions (P<0.001). Conclusion: within the limitations of this study, 1-month immersion of denture teeth in coffee, tea and cola solution altered the ∆E values; however, they were within the acceptable range, except for Beta Star. Turmeric solution caused unacceptable color change in all denture teeth even after 24 h of immersion.